Type Of Personality Theory Of Personality Through Employees With The Eysenk Work: Tipe Kepribadian Teori Kepribadian Melalui Pegawai Dengan Pekerjaan Eysenk - Hurriyati, Dwi; Agustina, Merry; Jemakmun, Jemakmun (Psikologia : Jurnal Psikologi, 2019)
Every company will use personality tests as a way to measure and evaluate potential employees. It is understood that there are several personality types that exist in each employee having a good type, trait, trait that will have an impact on the progress and excellence of an organization, and they ensure they make good choices. Therefore the purpose of this study is to find out the personality types that exist in the employees of Bina Darma University Palembang. This study uses 57 Eysenck Personality Inventory measuring instruments. This study uses quantitative methods. The sample used in this study were 320 employees of the University of Palembang Bina Darma. From the results of this study it was found that 70 employees had stable extroverted personality types in work, 64 employees had an introvert stable personality type, 56 employees had unstable introverted personality types, 40 employees had unstable extroverted personality types at work.